Lectotypification, geographic distribution and conservation status of Cephalanthus glabratus (Naucleeae-Rubiaceae) - Romero, María Florencia (2021)
Cephalanthus glabratus is an imperfectly known species of the family Rubiaceae. It is a medicinal plant widely used by the locals in its area of distribution, however until now it has received little attention from the scientific community, which is evidenced in the few articles treating the species. The species is a much-branched shrub, with whorled leaves, glomeriform inflorescences, schizocarpic fruits with 1-seeded mericarps, and seeds with a large spongy strophiole. It grows only in the vegetation of the lowlands and is always related to the basins of the main rivers of the region, Paraguay, Paraná, Uruguay and Río de la Plata, and therefore is strongly threatened by the human activities along them (hydroelectric dams, deforestation, advances of urban areas, reduction of the wetlands, etc.). Following IUCN guidelines and all available distributional data, we rated it NT (Near Threatened). Despite the fact that the genus was taxonomically revised, the nomenclatural type of Cephalanthus glabratus was not correctly clarified, so we have done so here. A detailed description, ecological and distributional data are provided.